The study of economic, political and social factors that affect on currency exchange estimation: a study on GBP against USD / Mohammad Nur Aiman Azahari - Azahari, Mohammad Nur Aiman (2021)
The study is about the estimation of GBP/USD trend and economy, social and political factors. The aims of the study are to determine the relationship between the GBP/USD estimation trend price and economy, social and political factors for two countries, United Kingdom and United States. The sample of data is collected from World Data Bank from range of year 2000 to 2019. The variables used include the yearly quoted price, Gross Domestic Product (GDP), LIBOR benchmark, Broad Money (M3) and Canadian Dollar (CAD). The method used in this research is panel data. The expected findings is to seek the correlation as well as positive relationship. The contribution of study are very useful for traders especially in forex market to gain historical information and predicting future target.